أثر استخدام التكنولوجيا الحديثة في إرساء تطبيق المبادئ الإسلامية الحاكمة للعمل الإنساني The Impact Of The Use Of Modern Technology In Establishing The Application Of Islamic Principles Governing Humanitarian Action - Al-Mulla, Ahmad Abdullah; Alzitawi, Diaya Uddeen Deab Mahmoud (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
In light of the rapid technological developments and the spread of poverty, disease, and natural disasters in the world, there was an urgent need to clarify the purposes of Islamic law governing humanitarian work and to clarify the true image of Islam in helping suffering humanity, and in light of the monopoly of rich capitalist countries on the wealth of the world. Therefore, this study aimed to identify the most important purposes established by Islamic law to govern humanitarian work, as well as to identify the impact of the use of modern technology (such as metaverse, artificial intelligence, drones, robots, and blockchain) on establishing the application of Islamic principles and practices for humanitarian work on the ground, and how can this technology be exploited to achieve social solidarity and enhance human communication as urged by Islam? The results of the study concluded that the Islamic Sharia has established several governing principles for humanitarian action, to achieve social solidarity, relief for the distressed, and removal of destitution for the needy, the most important of which are: Islam’s care and honoring of man, doing good, the universality and mercy of Islam, the brotherhood of humanity, equality, and partnership Humanity, which all pours into the crucible of enrichment humanitarian work and its prosperity. The study also concluded that modern technology has an effective positive impact in establishing the principles and practices of humanitarian work on the ground in light of the current digital age. Accordingly, the researcher recommends the need to find an effective mechanism to raise awareness of the purposes of Islamic law in humanitarian work in the world and keep pace with modern technological applications to be used in establishing the governing principles of Islamic charitable work. Keywords: Governing Principles In Islamic Law, Modern Technology, Metaverse, Drones, Blockchain.